Designing A Booklet of Local Folktales to Support Junior High School Students English Extensive Reading Activity - Kasangke, Gaela; Ikhsanudin, Ikhsanudin; Suhartono, Luwandi (Journal of English Education Program, 2025)
This research was aimed to design a booklet of local folktales to support junior high school ninth grade students English extensive reading activities as well as to help them to reach their reading objectives in classroom with the related reading topic. This research was a subject of an English teacher. The method used for this research was development research that used the first three phases of the ADDIE instructional model, namely the analysis, design, and development phases. We conducted the first interview, followed by documentation and observation to gather the data and used experts"™ recommendations and descriptive analysis to analyze the data. In the analysis phase, as the preliminary process of the research, we collected the data through interviews, documentation, and observation. In the design phase, we began to design a draft of the product. In the development phase, we started to develop a draft of the local folktales booklet followed by an internal evaluation. According to the findings of the research, it was indicated that the local folktales booklet was appropriate and able to support the students"™ English extensive reading activities as well as to be their supplementary reading material product to be used in the classroom.